Mitro‐aortic fibrosa pseudoaneurysm and concomitant aortic stenosis: How to kill two birds with a stone. Issue 9 (11th July 2020) - Boi, Alberto; Garau, Giovanni; Rossi, Angelica; Lixi, Giovanni; Armandi, Laura; Fele, Giovanna Salvatorica; Cossa, Stefano; Matta, Gildo; Manconi, Manlio; Sanna, Francesco; Loi, Bruno
Abstract: Pseudoaneurysm of mitral‐aortic intervalvular fibrosa (P‐MAIVF) is a rare acquired malformation of the mitral‐aortic intervalvular area. It appears as a pulsatile cavity in the mitral‐aortic junction communicating with the left ventricular outflow tract. P‐MAIVF has been reported as a complication of aortic and mitral valve surgery, infective endocarditis, and thoracic trauma. It is associated with life‐threatening complications. The recommended treatment is surgery, however, conservative therapy is an alternative approach for high‐risk patients or when surgical treatment is refused. We describe a successfully exclusion of a P‐MAIVF by transapical transcatheter aortic valve implantation in a patient with concomitant severe aortic stenosis.